Development and characterization of in vitro inducible immortalization of a murine microglia cell line for high throughput studies - Hana Yeh; Matthew A. De Cruz; Yang You; Seiko Ikezu; Tsuneya Ikezu (Scientific Reports)
Abstract There are few in vitro models available to study microglial physiology in a homeostatic context. Recent approaches include the human induced pluripotent stem cell model, but these can be challenging for large-scale assays and may lead to batch variability. To advance our understanding of microglial biology while enabling scalability for high-throughput assays, we developed an inducible immortalized murine microglial cell line using a tetracycline expression system. The addition of doxycycline facilitates rapid cell proliferation, allowing for population expansion. Upon withdrawal of doxycycline, this monoclonal microglial cell line differentiates, resembling in vivo microglial physiology as demonstrated by the expression of microglial genes, innate immune responses, chemotaxis, and phagocytic abilities. We utilized live imaging and various molecular techniques to functionally characterize the clonal 2E11murine microglial cell line. Transcriptomic analysis showed that the 2E11 line exhibited characteristics of immature, proliferative microglia during doxycycline induction, and further differentiation led to a more homeostatic phenotype. Treatment with transforming growth factor-β modified the transcriptome of the 2E11 cell line, affecting cellular immune pathways. Our findings indicate that the 2E11 inducible immortalized cell line is a practical and convenient tool for studying microglial biology in vitro.